Awake - Preston, Natasha (Naperville, Illinois : Sourcebooks Fire, 2015)
"A car accident causes Scarlett to start remembering pieces of an unfamiliar past. When a new guy moves into town, Scarlett feels an instant spark. But Noah knows the truth of Scarlett's past, and he's determined to shield her from it...because Scarlett grew up in a cult called Eternal Light, controlled by her biological parents. And they want her back"--
Keywords: Cults -- Juvenile fiction; Memory -- Juvenile fiction; Romance fiction; Families -- Juvenile fiction; Young adult fiction